Analisis scheduling pengerjaan reinforcement fuselage pesawat N219 menggunakan metode program evaluation and review technique (PERT) PT. Dirgantara Indonesia - priyono, agus; mauidzoh, uyuunul; astuti, marni (Institut Teknologi Dirgantara Adisutjipto, 2022)
One of the successes or failures of a project is influenced by project scheduling and control planning, less effective scheduling results in delays and the emergence of problems during project work, this requires good scheduling to regulate work activities, therefore determining the critical path of activities is needed to Set the time for the work to go according to plan. In this study, the focus is on scheduling the reinforcement fuselage for the aircraft N219 PT. Dirgantara Indonesia, using the Program Evaluation And Review Technique (PERT) method to determine the critical path of activity and calculate the most likely completion time of the reinforcement fuselage work. The results of the research analysis on the main schedule for the reinforcement fuselage work obtained a critical path with the activity code A – B – D – E – G, Development Problem Log (DPL) scheduling analysis obtained critical path A1 – B1 – C1 – E1 – F1, A2 – B2 – C2 – D2, A3 – B3 – D3 – E3, A4 – B4 – C4 – D4, A5 – B5 – C5 – D5 – E5, A6 – B6 – C6 – D6 – E6. And the most likely completion time for the reinforcement fuselage work is 40-45 days with a probability value of 95.72% - 99.88%.